The Weak Role of Prosecutors in Designating Justice Collaborators in Indonesia - Nugraha Ardi Setiawan; Setiawan Noerdajasakti; Faizin Sulistio (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Crime is a phenomenon that has infiltrated into communal life. One type of crime resulting from this development is criminal activities carried out in collusion or groups, meticulously planned, and referred to as organized crime. This type of crime can be categorized as an extraordinary or extraordinary crime because it is considered more extreme than ordinary crimes. In organized crime, perpetrators form a group that employs various detailed and synchronized methods to obtain money, power, or other objectives. Examples of organized crime include corrupt groups, robbery conspiracies, and even groups of murderers. This should prompt law enforcement agencies to undertake new efforts to address and combat this type of crime, and one of the means employed can be through the Criminal Justice System network.